The Star Atlas Companion What you need to know about the Constellations - Bagnall, Philip M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
The Star Atlas Companion is the ideal companion to any star atlas, as it is the first book to provide a true perspective on the characteristics and distances of over 1,100 stars and their movement through space. With the aid of scale diagrams, the reader can grasp difficult-to-understand concepts such as how far apart stars really are, their relative sizes, how fast they spin and their shapes, and how the constellation patterns change over time. This book: - describes many stars visible to the naked eye in both the northern and southern hemispheres; - explains binary and multiple star systems in detail; - gives the properties of many open clusters; - enables a true appreciation of the scale of our galactic neighborhood
About this book -- Acknowledgments -- Introduction -- Making sense of the data -- The Constellations -- Andromeda to Chamaeleon -- Circinus to Indus -- Lacerta to Pisces -- Piscis Australis to Vulpecula -- Index.
Keywords: Physics; Astronomy; Physics; Astronomy, Observations and Techniques; Popular Science in Astronomy